UKRAINE IN GERMAN FOREIGN POLICY DURING THE ACTIVE PHASE OF THE RUSSIAN-UKRAINIAN WAR (Вісник: Міжнародні відносини, 2025)
Background. The paper analyzes the conceptual foundations and main directions of German policy towards Ukraine during the active phase of the Russian-Ukrainian war. A particular attention is paid to the assistance of Germany to Ukraine in repelling the Russian aggression.Methods. The research methodology is based on a combination of the systemic approach, historical and structural-functional analysis, comparative studies, and analytical forecasting.Results. An attempt is made to scientifically understand the changes that occurred in German foreign policy under the influence of the Russian-Ukrainian war transition into an active phase and the occupation by Russia of significant territories in the east and south of Ukraine, which made this armed conflict the most powerful in Europe since World War II. A comparison is made of the policy towards Ukraine of the German governments led by O. Scholz and F. Merz. The special attention is paid to the assistance of Germany to Ukraine in repelling the Russian aggression. The evolution of German approaches to the large-scale Russian aggression against Ukraine is revealed. The tools, forms and methods of Germany's support for the Ukrainian state are analyzed.Conclusions. It is shown that the hybrid Russian aggression was only gradually perceived by Western states, including Germany, as a direct threat to the eastern flank of the EU and NATO. It is proven that in the conditions of the Russian-Ukrainian war, Germany's cooperation with Ukraine has become an important element in strengthening the defense capabilities of our state and its integration into the European and Euro-Atlantic security institutions. It is predicted that in the future the main tasks of bilateral relations will envisage the further integration of Ukraine into the European structures, strengthening the military-political cooperation and joint development of new security initiatives using Ukrainian experience in conducting a modern warfare.